2003
DOI: 10.1088/0964-1726/12/5/301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of complex crack damage for honeycomb sandwich plate using wavelet analysis and neural networks

Abstract: In this study, crack damage detection for a honeycomb sandwich plate is studied using the energy spectrum of dynamic response decomposed by wavelet transform and the artificial neural network (NN). The results show that taking the energy spectrum of the decomposed wavelet signals of dynamic responses as the inputs of the NN can simplify the NN design for structural damage detection and it possesses a high sensitivity to small damage. Experimental results also show that the NN designed in this study can accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Materials with periodic pore structures are widely used as sandwich structures because of light weight, strong strength and stiffness. Due to the low density and low thermal conductivity of sandwich core structure materials can perform anisotropic design and manufacture according to special requirements, and the combination of stealth technology and sandwich core structures can form a dual functional structure that can not only carry load but also transmit wave, therefore, it has attracted much attention in aviation, aerospace and other fields 5–10 …”
Section: Figurementioning
confidence: 99%
“…Materials with periodic pore structures are widely used as sandwich structures because of light weight, strong strength and stiffness. Due to the low density and low thermal conductivity of sandwich core structure materials can perform anisotropic design and manufacture according to special requirements, and the combination of stealth technology and sandwich core structures can form a dual functional structure that can not only carry load but also transmit wave, therefore, it has attracted much attention in aviation, aerospace and other fields 5–10 …”
Section: Figurementioning
confidence: 99%
“…Recently, some researchers have reported new methods to evaluate the dynamic responses of sandwich structures. Yam et al (24) studied crack detection in the facesheet of a honeycomb sandwich structures using energy spectra of the dynamic responses decomposed by wavelet transform and an artificial neural network (ANN). Nichols et al (25) showed a procedure for detecting impact damage in foam core sandwich utilizing concepts from the field of information theory.…”
Section: Damage Detection Using Dynamic Responsementioning
confidence: 99%
“…In other cases, structural response is analyzed using techniques for signal processing, as the wavelet transform, to recover structural parameters and, from them, to determine possible structural damage. () In other works, damage detection is studied as a parameter identification problem where the stiffness, mass, and damping coefficient are recovered and then used to obtain the natural frequencies and mode shapes. For example, in Ling et al() and Kuwabara et al,() an autoregressive with exogenous input model is used to identify the stiffness of all the stories.…”
Section: Introductionmentioning
confidence: 99%